The Relevance of Indonesian Archipelagic Arts and Culture as an Effective Instrument of Dakwah in the Modern Era - Qonitah Nurul Rahmah; Raisya Rabiah; Khomisah Khomisah (Fakultas Dakwah UIN KHAS Jember, 2026)
Art in the Islamic perspective is not merely understood as an aesthetic expression but also as an effective medium for conveying moral and spiritual values to society. In the context of da’wah, a persuasive and culturally grounded approach through art serves as a strategic alternative for disseminating Islamic teachings without coercion, as exemplified by the Wali Songo through wayang performances in Java. This study aims to analyze the role of art as a medium of da’wah in the dissemination of Islamic values and to identify its forms and relevance in the modern era. The research employs a descriptive qualitative approach using a library research method, analyzing various relevant literature on art and da’wah. The findings indicate that art has significant potential as an effective medium of da’wah, both through traditional forms such as Islamic music, calligraphy, literature, and performing arts, as well as through modern platforms including film, digital media, and contemporary music. Art enables the delivery of Islamic messages in an emotional, communicative, and adaptive manner, thereby contributing substantially to reaching diverse segments of society, particularly the younger generation.